Transgenic Reduction of Cytokinin Levels in Roots Inhibits Root-Sprouting in Populus . Issue 4 (31st May 2019) - Li, Wei; Zhai, Longmei; Strauss, Steven H.; Yer, Huseyin; Merewitz, Emily; Chen, Junmei; Wang, Xiaomin; Zhuang, Weibing; Fang, Chu; Chen, Yingnan; McAvoy, Richard; Han, Zhenhai; et al.
Abstract : An analysis of a root-sucker–repressing technology for poplar plants that reduces root cytokinin contents. Abstract: Root sprouts—the formation of new shoots from roots—is an important mechanism for local gene flow from poplar ( Populus spp). An effective strategy to reduce root sprout formation could therefore help to ensure containment during field research and commercial deployment of poplar when grown as exotic or transgenic forms. We used a flavonoid glycosyltransferase gene promoter from Scutellaria barbata ( SbUGT ) to drive the expression of AtCKX2, a cytokinin oxidase from Arabidopsis that converts active to inactive cytokinins in roots of poplar. In the greenhouse, SbUGT :: AtCKX2 transgenic plants exhibited a similar shoot growth habit, but had enhanced root growth and fewer root sprouts, compared to the wild-type control and transgenic events with low transgene expression in roots. Under field conditions, the transgenic trees also had similar growth habits and stem growth rates that were not statistically different from wild-type trees over 3 years. Removal of trunks generally induced high rates of root sprouting; however, in selected SbUGT :: AtCKX2 transgenic poplar events there was an absence or fewer root sprouts compared to wild-type trees, consistent with the greenhouse results. Our study demonstrates that the SbUGT :: AtCKX2 gene can effectively inhibit root sprouting of poplar trees under field conditions, and thus may provide a useful tool to address concerns associated with root-sprouting-mediated transgene spread.